Exploring Vocabulary Retention and Student Engagement: A Dive into Gamified vs. Traditional Flipped Classroom - Iis Sujarwati; Dedi Sofyan; Marzon Efendi; Muhammad Nafi Annury (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2025)
This study compares the Gamified Flipped Classroom (GFC) model to the Traditional Flipped Classroom (TFC) model on vocabulary retention and student engagement in 76 students. This study examined if the two teaching approaches differed in vocabulary and student engagement. Both groups' vocabulary retention increased after the intervention, with the experimental group scoring 78.45 compared to 76.89 for the control group. Independent sample t-tests showed statistically significant improvements in both groups’ post-test scores (p < 0.001), but no significant difference was found between them, leading to the rejection of Hypothesis 1. GFC had better mean Likert-scale values for student involvement (4.32) than TFC (3.76). The Mann-Whitney U test demonstrated substantial engagement differences between groups. Although the GFC model had certain drawbacks, qualitative data from the open-ended survey and focus group talks showed numerous positive student opinions. GFC increases student involvement, but both teaching approaches improve vocabulary retention, according to study.